Pruritus in burn victims: relationship with anxiety, depression, and post-traumatic stress (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To assess the relationship between pruritus intensity and anxiety, depression, post-traumatic stress, and health-related quality of life scores in burn victims. Methods: A cross-sectional study, carried out in two outpatient clinics of burn hospitals located in municipalities in the countryside of São Paulo. The sample consisted of 60 patients who answered sociodemographic and clinical characterization instruments: the Visual Numerical Scale, to assess pruritus intensity, the Hospital Anxiety and Depression Scale, the Impact of Events Scale, to assess post-traumatic stress, and the Freiburg Life Quality Assessment Wound Module to Brazilian Portuguese. Results: The sample was characterized by a predominance of males (73%). Significant positive correlations were found between pruritus intensity and anxiety (r=0.33), depression (r=0.53), post-traumatic stress (r=0.43), and total Freiburg Life Quality Assessment Wound score (r=0.63). Conclusions: These findings reinforce the importance of assessing pruritus in comprehensive care for burn victims, aiming to reduce the psychological impact and improve health-related quality of life.